Venturi mask is the pioneer of High-Flow Oxygen Therapy Concepts - Matteo Manici; Stefano Bambi; Alberto Lucchini (Infermieristica Journal)
Oxygen therapy should be carefully considered and monitored because, as any other medications, it can cause harm to patients, if used inappropriately. This paper focus on the distinction between low-flow and high-flow oxygen therapy. A discussion about Venturi system for oxygen administration is carried on, given that some authors include it in the low-flow devices group despite its characteristics to deliver high flow therapy.